Fetal Vibroacoustic Stimulation in Computerized Cardiotocographic Analysis: The Role of Short-Term Variability and Approximate Entropy - Maria Laura Annunziata; Mariamaddalena Scala; Natascia Giuliano; Salvatore Tagliaferri; Olga Carmela Maria Imperato; Francesca Giovanna Esposito; Marta Campanile; Andrea Di Lieto (Journal of Pregnancy)
The aim of this study was to evaluate the impact of vibroacoustic stimulation (VAS) on computerized cardiotocography short-term variability (STV) and approximate entropy (ApEn) in both low- and high-risk pregnancies. VAS was performed on 121 high- and 95 low-risk pregnancies after 10 minutes of continuous quiet, while their FHR parameters were monitored and recorded by cCTG analysis. Fetal heart rate was recorded using a computer-assisted equipment. Baseline FHR, accelerations, decelerations, STV, long-term irregularity (LTI), ApEn, and fetal movements (FMs) were calculated for defined observational periods before VAS and after 10 minutes. Data were also investigated in relationship with the perinatal outcome. In each group of patients, FHR after VAS remained almost unmodified. Fetal movements significantly increased after VAS in both groups. Results show that only in the high-risk pregnancies, the increase of STV and the decrease of ApEn after VAS were significantly associated with favorable perinatal outcomes.